Asymmetric synthesis of aryloxypropanolamines via OsO4-catalyzed asymmetric dihydroxylation - Sayyed, I. A.; Thakur, V. V.; Nikalje, M. D.; Dewkar, Gajanan; Kotkar, S. P.; Sudalai, A. (Tetrahedron, 2005)
A simple and effective procedure for the enantioselective synthesis of several beta-adrenergic blocking agents incorporating the first asymmetric synthesis of celiprolol, is described. The key steps are (i) sharpless asymmetric dihydroxylation of aryl allyl ethers to introduce chirality into the molecules and (ii) conversion of cyclic sulfates into the corresponding epoxides using a three-step procedure. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: antihypertensive; asymmetric dihydroxylation; cyclic sulfates; epoxides

Asymmetric synthesis of (R)-(-)-baclofen via asymmetric dihydroxylation - Thakur, V. V.; Paraskar, A. S.; Sudalai, A. (Indian Journal of Chemistry Section B-Organic Chemistry including Medicinal Chemistry, 2007)
A short and efficient asymmetric synthesis of (R)-(-)-baclofen, a selective GABA(B) agonist has been described with an overall yield of 14% and 85% ee. The Os-catalyzed Sharpless asymmetric dihydroxylation of alpha,beta-unsaturated olefin constitutes the key step in introducing stereogenic centers into the molecule.
Keywords: asymmetric dihydroxylation; baclofen; cyclic sulfate; gamma-aminobutyric acid; Parkinsons' disease